Spatial Distribution of Dissolved Heavy Metals (Hg, Cd, Cu, Pb, Zn) on the Surface Waters of Pare Bay, South Sulawesi - Ulung Jantama Wisha; Aida Heriati; Muhammad Ramdhan; Eva Mustikasari; Herdiana Mutmainah; Ilham Ilham (Marine Science Department Diponegoro University, 2018)
Pare bay is one of the areas of significance which is utilized for port services, stevedoring, oil distribution, regional industrial development, aquaculture, cultivation and settlement systems. Pare Bay potentially has a good prospect for a gigantic development. Whilst, a very dangerous threat is pollution, especially heavy metal pollution and water quality degradation. This study aims to determine the current condition of heavy metal concentrations and its distribution on surface waters of Pare Bay. Heavy metals were analyzed using AAS (Atomic Absorption Spectrophotometry) in which it has a minimum detection limit reached 0.001 ppm so that the heavy metal concentration can be well-determined. Hg concentration is higher in the surface ranged 0.01-0.1 mg.l-1. Cd concentration ranged from 0.018-0.083 mg.l-1. Cu concentration ranged from 0.043-0.078 mg.l-1. Pb concentration ranged from 0.111-2.692 mg.l-1. Zn concentration ranged from 0.004 - 0.112 mg.l-1. Heavy metals content in Pare Bay exceeds the standard quality established by Ministry of Environment. It potentially harms the marine life which indirectly reduces the function value of Pare Bay as a center of maritime in the South Sulawesi. Water quality condition play a role in inducing the toxicity level of heavy metals in the Pare Bay. So that this area need to be monitored the water quality sustainably.